Wind Tunnel Test : Whether Between Simplified And Detailed Model Shows Any Difference In Coefficience Of Drag And Lift - Mior Mohd Amin, Mior Lokman (UTeM, 2008)
This paper presents the verification to the fact that whether a simple model shows any different in terms of drag and lift value compared to the detail model when tested using wind tunnel. The models have been scaled down to 1:25 ratio and will be tested in atmosphere condition. Commonly, for wind tunnel testing, the model been used has been stripped and simplified for some reason, mostly because on a small model the difference is not significance. It is to proof whether the ignorance could affect the experiment or have any direct impact to the drag force and lift force value and at the same time giving difference in the Coefficient of Drag and Lift.